Peningkatan Kapasitas Produksi dan Diversifikasi Produk Melalui Mesin Baru dan Inovasi Menu Sehat - Firdaus Al Maidah; Via Lailatur Rizki; Ria Meilan (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
This community service program aims to empower members of the Dharma Wanita Persatuan SMPN 1 Rowokangkung through the management of a healthy canteen as part of efforts to improve economic welfare. Although this canteen has great potential, partners face challenges such as limited production capacity, lack of product variety, and inability to prepare financial reports that meet standards. To overcome these problems, this program offers solutions that focus on three main aspects: 1) Increasing production capacity through the procurement of new machines, such as cup sealer machines, freezers, and electric ovens; 2) Product diversification with the innovation of six new healthy and attractive menus for students, which are implemented through training and technology application; and 3) Increasing partners' understanding and skills in preparing financial reports based on Financial Accounting Standards for Micro, Small, and Medium Entities. The implementation method consists of five stages: socialization, training, technology application, mentoring, and evaluation, as well as program sustainability efforts. This program has succeeded in increasing the production capacity of the healthy canteen, where daily production has increased by more than 50% thanks to new machines. Product diversification added six healthy menu variations that were more attractive to consumers, thus increasing the appeal of the canteen. In addition, partner members showed significant improvements in their ability to prepare more transparent and standardized financial reports, with average test scores increasing from 53 to 93 after the training. Overall, this program improves the economy of partner members and contributes to creating a healthier school environment. The program's sustainability is driven by the partners' commitment to continue developing healthy canteens, making it a real effort to empower the economy and welfare of the school community.